Effects of high temperature shocks applications on seed viability and germination in some Anatolian Black Pine [Pinus nigra J.F. Arnold ssp. pallasiana (Lamb.) Holmboe] populations - Sezgin Ayan; Cihan Erkan; Esra Nurten Yer Çeli̇k; Orhan Gülseven; Şeyma Selin Akın; Ergin Yılmaz (Turkish Journal of Forestry, 2020)
Forest fires are a frequent event in Mediterranean climate-dominated regions and have great importance on succession. This reality, which is also valid for forest trees, facilitates the regeneration of some species and causes some species to lost their presence in the area. Therefore; it is important to know the fire ecology of the each species. To know the effects of the fires on seed viability and germination; will facilitate the development and follow-up of existing species in the area. In this study, different heat shocks (70, 90, 110 and 130 ºC) at different durations (1 and 5 min.) were applied on seeds obtained from 15 different populations of Anatolian black pine [Pinus nigra J.F. Arnold ssp. pallasiana (Lamb.) Holmboe] from four different main breeding zones and germinations was followed. As a result, the treatment of 130°C-5 min. reduced germination ability of seeds. However, it was found that Anatolian black pine seeds can withstand high heat shocks without affecting the germination ability up to 110 ºC. In addition, it was found that 1 min. heat shock application did not decrease the germination ability. Among the populations Sütçüler-Tota (1600 m), Çal-İnceler (1560 m), Alaçam-Gölcük (1050 m) Bursa (950 m) and Domaniç-Dereçarşamba (1400 m) populations have shown the highest germination capacity as general mean. And the treatments of 70ºC-5 min, 90ºC-1 and 5 min, 110ºC-1 min and 130ºC-1 min among the applications increased germination percentage according to the control group.
Keywords: anatolian black pine; population; popülasyon; Forestry; SD1-669.5; heat shock; germination; çimlenme; anadolu karaçamı; sıcaklık şoku; 2. Zero hunger; 15. Life on land